Analyzing of Morphometric Parameters and Designing of Thematic Maps Using Raster Geoprocessing Tool - Hazir S. Çadraku (Salehan Institute of Higher Education, 2022)
GIS techniques, digital elevation models (DEM), raster geoprocessing tools, and software such as ArcMap are a quick and simultaneous solution for the assessment, measurement, and analysis of morphometric parameters of river basins. This paper aims to show the use of the Digital Elevation Model and the ArcGIS program for the analysis of morphometric parameters and the construction of a set of thematic maps needed for spatial planning, water resources management, and similar purposes. Through these techniques, 18 morphometric parameters were determined and analyzed in the study area, which is located in the central part of the Republic of Kosovo and covers an area of 38 km2, and 15 thematic maps were constructed. The altitude of the area varies from 544 m to 1019 m, the slope from <5% to > 24%, with a total number of stream segments of 601 and a drainage density of 5.02 km/km2. The analysis of morphometric parameters presents an important indicator regarding the space and other elements of the river basin. Doi: 10.28991/CEJ-2022-08-09-06 Full Text: PDF